(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2024)
Electric vehicles are already known but simultaneously new. In the last decades, an important evolution has been seen in electric energy storage systems, motor control, and the design of electric motors. The present paper aims to illustrate some examples of laboratory works implemented at the university didactical level. It emphasizes the importance of choosing an adequate electric powertrain as an integrated system, but also the role of the powertrain components for the performance of the electric vehicles. The program’s implementation involves simulation tools for the vehicle and the powertrain components, but also physical platforms integrating direct current, asynchronous, and synchronous motors.